Empirical Modelling of Drying Characteristics of Elongate Glassy Perchlet (Chanda nama) (Hamilton, 1822) in Solar Hybrid Dryer - Alfiya, P. V.; Murali, S.; Delfiya, D. S. Aniesrani; Samuel, Manoj P. (Fishery Technology, 2018)
This study was conducted to evaluate the performance of solar dryer with electrical back-up to produce quality dried Glassy perchlet (Chanda nama). Insolation of the experimental region varied from 25 to 1025 W m-2. Atmospheric temperature showed a variation between 29.5 to 34.5Â°C. Relative humidity outside the dryer ranged from 56 to 76.5% showing a direct relationship with temperature. Drying experiment was carried out for 10 h at drying air temperature of 60Â°C. Relative humidity and velocity of drying air inside the drying chamber was 68% and 0.8 m s-1 respectively. Drying conditions were maintained inside the dryer by electrical back-up. Weight loss of pre-processed C. nama during drying was measured at 1 h duration. Drying characteristic data were fitted into empirical drying models. Two-term model was found to be the best fit for the drying characteristic data under specified conditions (R2=0.998, RMSE=0.016 and Ï‡2=0.00027).